150k views
4 votes
Solve for u.
4+3u = -2
Simplify your answer as much as possible.

2 Answers

4 votes

Answer:

u=−2

Step-by-step explanation:Step 1: Simplify both sides of the equation.

3u+4=−2

Step 2: Subtract 4 from both sides.

3u+4−4=−2−4

3u=−6

Step 3: Divide both sides by 3.

3u

3

=

−6

3

u=−2

User Mbeacom
by
5.7k points
1 vote

Answer:

-2

Explanation:

4+3u=-2

3u=-2-4

u=-6/3

u=-2

User Fritzmg
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.